The utilization of PET/CT and production of radiopharmaceuticals at Landspitali – The National University Hospital of Iceland - Oddný Árnadóttir 1994- (2021)
Introduction: Positron emission tomography/Computer tomography (PET/CT) is a new diagnostic medical imaging technology in Iceland located at Landspitali – The National University Hospital of Iceland. The PET/CT scanner and the radiopharmaceutical unit's production have been operational for nearly two years. The radiopharmaceutical (RP) production currently produces two radiotracers, 18F-FDG and 18F-Flutemetamol. Objective: The study aimed to observe PET/CT's utilization and the production of radiopharmaceuticals at Landspitali for two periods and assess whether it is possible to utilize both PET/CT and radiopharmaceuticals better by implementing other radiotracers and studies in the future. Methods: The study was retrospective, where the data was extracted from the records at Landspitali, Department of Radiology and Department of Clinical Physiology & Nuclear Medicine, from two six-month periods (01.08.2018 – 31.01.2019 and 01.08.2019 – 31.01.2020). A questionnaire was sent to medical specialists to understand their interests better and their input regarding the PET/CT scanner and RP production. Results: Total patients undergoing PET/CT scan in period 1 was 220, and period 2 was 379, which was a significant increase of 72.27% between periods. The total production days that were approved and scheduled for PET/CT scan also showed a significant increase of 42.22% between periods. The total activity of 18F-FDG production increased significantly, while the remaining activity of 18F-FDG remained stable between periods, while a significant amount of activity that was wasted, which could have been used for additional patients. The participation in the survey was 16.2%, the majority of the responses showed that there is much need for improving information flow between the PET/CT and the RP units to medical specialists and there is interest and demand among medical specialist to introduce new radiotracers. Conclusion: Both the PET/CT scan and radiopharmaceutical production increased in period 2 due to higher clinical ...